Conventional and advanced exergy analyses of an organic Rankine cycle by using the thermodynamic cycle approach - Yi Wang (Wiley, 2021)
Abstract In this study, a basic organic Rankine cycle (ORC) is introduced in an air separation process for waste heat recovery. Conventional and advanced exergy analyses are adopted to investigate the thermodynamic properties of components in the ORC. A comprehensive thermodynamic model is constructed to improve the advanced exergy analysis in the ORC, thereby encompassing real, theoretical, unavoidable, and hybrid cycles. Nine organic working fluids are introduced to investigate the influence on the ORC performance. (1) The conventional exergy analysis reveals the following: (a) The expander constantly demonstrates the maximum exergy efficiency except when R227ea is used. (b) The evaporator constantly exhibits the maximum exergy destruction regardless of the working fluid used. (c) The maximum product exergy is obtained when R114 is used. (d) Key components must focus on the condenser and evaporator to improve the ORC performance. (2) The advanced exergy analysis reveals that the expander demonstrates maximum potential for improvement because its endogenous avoidable exergy destruction accounts for approximately 90% of its real exergy destruction for all working fluids. The expander must be improved to achieve the optimal ORC performance. The advanced exergy analysis can distinguish the source of exergy destruction and the magnitude for possible improvement via the proposed thermodynamic model in this study. The comprehensive thermodynamic model can promote the investigation of the advanced exergy analysis in the ORC. Applying conventional and advanced exergy analyses to investigate the thermodynamic performance of a system or its components is highly recommended.